Cultural features of the of riddles in Uzbek and English languages (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
Riddles can be researched in many ways, specifically, metaphorical features by its grammatical rules. Lexical similarities between Uzbek and English riddles were examined in this paper, along with characteristics of riddles that have been viewed from various angles by scientists. There are similarities and differences within riddles in terms of their structure, articulation style, and content. The similarity implies that they are both the result of mythological and traditional creation. This article examines the similarities and differences between riddles written in two languages